Sex differences in brain regional homogeneity during acute abstinence in cocaine use disorder. (23rd April 2022) - Sanvicente‐Vieira, Breno; Rothmann, Leonardo Melo; Esper, Nathalia Bianchini; Tondo, Lucca Pizzato; Ferreira, Pedro Eugênio; Buchweitz, Augusto; Franco, Alexandre Rosa; Grassi‐Oliveira, Rodrigo
Abstract: There are significant sex differences in the clinical characteristics of cocaine use disorder (CUD). As this is a brain disorder that involves changes in functional connectivity, we investigated the existence of sex differences among people with CUD and controls. We used a data‐driven method comparing males ( n  = 20, CK‐M) and females with CUD ( n  = 20, CK‐F) and healthy controls (20 males, HC‐M and 20 females, HC‐F). The participants undertook a resting‐state functional magnetic resonance imaging exam. Regional homogeneity (ReHo) was performed to identify group and sex differences. Persons with CUD of both sexes presented lower ReHo parameters than controls, especially within the parietal lobule. Males with CUD showed higher ReHo than females in three right‐side brain areas: postcentral gyrus, putamen and fusiform gyrus. It was found that abstinence symptoms severity was associated with lower ReHo values in the right postcentral gyrus and the right fusiform gyrus. Participants with CUD exhibited altered ReHo parameters compared to controls, similar to what is found in ageing‐related disorders. Our data also indicate that cocaine has sex‐specific effects on brain functioning when analysing ReHo. Abstract : Participants with cocaine use disorder (CUD) exhibited altered regional homogeneity (ReHo) parameters compared to controls, similar to those found in samples with ageing‐related disorders. Specific sex differences were identified within cocaine groups, where men show higher ReHo in brain regions related to sensory awareness, memory and emotion recognition. We described the role of the right postcentral gyrus and right fusiform gyrus in cocaine severity withdrawal symptoms.